Effect of substrate alloy composition on the oxidation behaviour and degradation of aluminide coatings on two Ni base superalloys. (1st May 2020) - Leng, W.; Pillai, R.; Naumenko, D.; Galiullin, T.; Quadakkers, W.J.
Highlights: Depletion processes of aluminide coatings on two Ni base superalloys studied. Base alloy composition strongly affected the microstructural degradation of coatings. Successful thermodynamic-kinetic model description of the aluminide coating depletion. Abstract: The oxidation behaviour and microstructural evolution of aluminide coatings on the Ni base superalloys Rene 80 and alloy 625 were investigated during 1050 °C oxidation in air. Alumina based oxide scales formed on the coating surfaces of both alloys and only minor differences in scale growth and spallation kinetics were found. A coupled thermodynamic-kinetic model was employed to describe the effect of the base material on the depletion processes and microstructural changes in the aluminide coating thus providing a tool for coating life time prediction without very extensive test programs.